2011
DOI: 10.1590/s1809-98232011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das instituições de longa permanência para idosos do município de Olinda-PE

Abstract: OBJETIVO: Este trabalho se propõe a analisar a organização e funcionamento das instituições de longa permanência para idosos (ILPI) do município de Olinda-PE, através da aplicação do instrumento específico da Vigilância Sanitária, elaborado em 2007, verificando se as instituições atendem à normatização do Ministério da Saúde. MATERIAIS E MÉTODOS: Estudo exploratório de abordagem quantitativa, realizado em sete ILPIs particulares, públicas e/ou filantrópicas do município de Olinda-PE. Foram respeitados os aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
0
8
0
7
Order By: Relevance
“…16 Entende-se que a faixa etária dos mais velhos é pontuada por particularidades e, assim sendo, devem ser implementadas ações que visem adequar as equipes em termos de número de profissionais e capacitação dos recursos humanos, para melhor atenção aos idosos, refletindo na melhoria de sua qualidade de vida.…”
Section: Mais Horas Para O Trabalho Em Ilpis Diante Da Dificuldade Emunclassified
“…16 Entende-se que a faixa etária dos mais velhos é pontuada por particularidades e, assim sendo, devem ser implementadas ações que visem adequar as equipes em termos de número de profissionais e capacitação dos recursos humanos, para melhor atenção aos idosos, refletindo na melhoria de sua qualidade de vida.…”
Section: Mais Horas Para O Trabalho Em Ilpis Diante Da Dificuldade Emunclassified
“…Women predominated, corroborating the findings of other studies which have presented demographic aspects of the institutionalized and non-institutionalized elderly population. 6,8,[13][14][15][16][17] The proportion of women on waiting lists before the exclusion criteria were adopted for this survey was 64%, higher than the proportion of females in the elderly Brazilian population, which is 55.8%, 17 reflecting cultural and familial structure factors. Culturally, women are more involved with caring, visit Family Health Units most often 18 and are also less likely to have a second family after divorce/separation or widowhood.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of other studies have found averages lower than this. 6,13,14,16 According to Mincato & Freitas,6 this fact may reflect an era when educational programs were more limited and there were higher levels of exclusion of access to basic education, especially among women.…”
Section: Discussionmentioning
confidence: 99%
“…8 In another study, with data from Olinda city/PE, 57.1% of institutions were philanthropic, 28.6% private and 14.3% mixed. 12 The main source of income of Brazilian LSIE is the monthly payment by residents, including philanthropics. Considering the institutions together, around 57% of income is obtained from the contribution or monthly payment; other 20% comes from public funding, while the own resources of the institutions account for about 12.6% of total.…”
Section: Institutional Diagnosismentioning
confidence: 99%
“…13 In Olinda, 85.7% of LSIE of that city used the retirement of residents for their maintenance. 12 Most of the resources in all Brazilian LSIE is destined to expenses with employees or service providers, regardless of their legal status, corresponding to 52.2% of total spending. About 14% of the total are for food, and 9.3% to the payment of fixed expenses (water, telephone, gas).…”
Section: Institutional Diagnosismentioning
confidence: 99%